Elucidating the Odor-Active Aroma Compounds in Alcohol-Free Beer and Their Contribution to the Worty Flavor - Piornos, José A. (J Agric Food Chem, 2020)
[Image: see text] Alcohol-free beers (AFBs) brewed by cold-contact fermentation exhibit a flavor reminiscent of wort which affects consumer acceptability. The aims of this study were to identify the odor-active compounds in AFB and elucidate the contribution of these to the overall aroma and worty character of the beer. Using a sensomics approach, 27 odor-active aroma compounds were identified and quantitated using gas chromatography–mass spectrometry. The most odor-active compound was methional (boiled potato-like aroma), followed by 3-methylbutanal (cocoa-like), (E)-β-damascenone (apple, jam-like), 5-ethyl-3-hydroxy-4-methyl-2(5H)-furanone (curry, spicy-like), and phenylacetaldehyde (floral, honey-like). The important contribution of these flavor compounds to the worty and honey aroma of AFB was determined by sensory assessment of the recombinate in a beer-like matrix with omission tests. The role of 5-ethyl-3-hydroxy-4-methyl-2(5H)-furanone in AFB aroma was reported for the first time. The outcomes from this study are of relevance for the brewing industry to design strategies for the reduction of the wortiness of AFB.